Depressive symptoms in Rheumatoid Arthritis patients in a general hospital setting in Kuching / Joven Mailvaganam - Joven, Mailvaganam (2019)
Rheumatoid Arthritis is a common, chronic and debilitating autoimmune illness with long-term physical and psychological implications to sufferers. The comorbid diagnosis of depression is a well-known entity in patients with Rheumatoid Arthritis but remains unrecognized due to the lack of vigilance on the part of the clinician. This study was conducted to establish the prevalence of depression among patients with Rheumatoid Arthritis. We had also aimed to determine the association between sociodemographic profile and clinical parameters of Rheumatoid Arthritis patients with symptoms of depression. Next, we intended to understand the link between disease severity of Rheumatoid Arthritis and symptoms of depression. Finally, we evaluated the association between functional status in Rheumatoid Arthritis and the presence of depressive symptoms. This is a hospital-based cross-sectional study on Rheumatoid Arthritis patients in Hospital Umum Sarawak. Convenience sampling was used in this study. Ethics approval was obtained from the Malaysian Ethics and Research Committee (MREC). Patients who consented to the enrolment into this study were given Hospital Anxiety and Depression Scale (HADS) Questionnaire and Health Assessment Questionnaire vi (HAQ). Disease Severity of Rheumatoid Arthritis was evaluated and scored with the Disease Activity Score-28 (DAS-28). Socio-demographic and clinical data were also obtained. Patients who were diagnosed with depression based on HADS were further evaluated with MINI International Neuropsychiatric Inventory (MINI) to confirm diagnosis of Major Depressive Disorder and referred to the psychiatry clinic. The prevalence of depression and patients who reported depressive symptoms was determined. Univariate and multivariate analysis were done to determine the association between depressive symptoms and correlates. Results : A total of 207 patients were recruited in this study. The prevalence of depression in Rheumatoid Arthritis was 1.5% (n=3). However, 38.7% (n=80) of patients reported having at least one symptom of depression. Apart from the status of cardiovascular disease (One-way ANOVA, p=0.032), other Rheumatoid Arthritis clinical parameters and medical comorbidities were not associated with depressive symptoms. Finally, socio-demographic data (such as age, sex, marital status, education level and employment) were not associated with symptoms of depression. Following multivariate analysis, functional status (based on HAQ score) in Rheumatoid Arthritis was found to be significantly associated with symptoms of depression (ANCOVA, p<0.001). Interestingly, disease severity (based on DAS-28 score) of Rheumatoid Arthritis was no longer associated with depressive symptoms (ANCOVA, p=0.697). Conclusion Although the prevalence of depression was low, more than a third of patients had some form of symptoms of depression. There was a significant association between functional status of Rheumatoid Arthritis patients towards symptoms of depression. However, vii there was no association between Rheumatoid Arthritis disease severity and depressive symptoms. Therefore, the author recommends the routine screening for depression and a more rigorous approach to the improvement of functional status in Rheumatoid Arthritis patients to minimize the risk of depression. Finally, a larger population and prospective longitudinal study is also recommended in future research in the region.